Effect of Ethylene-Vinyl Acetate Copolymer on Properties of Acrylonitrile-Butadiene-Styrene/Zinc Oxide Nanocomposites - Sirirat Wacharawichanant; Lalitwadee Noichin; Sutharat Bannarak (ASEAN Journal of Chemical Engineering, 2013)
Mechanical and morphological properties of acrylonitrile-butadiene-styrene (ABS)/zinc oxide (ZnO) nanocomposites used ethylene-vinyl acetate copolymer (EVA) as compatibilizer were investigated. The ABS/ZnO nanocomposites without and with EVA 4 wt% were prepared by melting-blend with an internal mixer. The results showed that the addition of ZnO nanoparticles did not improve the mechanical properties of ABS/ZnO nanocomposites. The impact strength of the ABS/ZnO nanocomposites decreased with increasing ZnO content. The addition of EVA in ABS showed a decrease the impact strength but increased after adding ZnO in ABS/EVA matrix. The ABS/ZnO nanocomposites with EVA was higher the percent strain at break, but lower Young’s modulus, tensile strength and impact strength than the neat ABS and ABS/ZnO nanocomposites. The percent strain at break of ABS/ZnO nanocomposites increased with incorporation of EVA all ZnO compositions. However, the poor compatibility between ethylene in EVA and ABS matrix reduced as most of the mechanical properties of ABS/EVA/ZnO nanocomposites. The ZnO particle distributions in nanocomposites were studied by scanning electron microscopy (SEM), which observed that ZnO particles agglomerated in ABS and ABS/EVA matrix. The fractured surfaces of impact test samples were also observed through SEM and revealed that the ductile fracture of ABS was converted to brittle fracture with addition of ZnO.